Detection of Ralstonia solanacearum in ginger rhizomes using post-enrichment NCM-ELISA - Priou, A Kumar, Y R Sarma, S (Journal of Spices and Aromatic Crops, 2002)
Bacterial wilt, caused by Ralstonia solanacearum, is an important production constraint in ginger. The pathogen is seed rhizome borne and the low level of inoculum is very difficult to be detected and monitored by conventional methods. Pathogen detection and selection of healthy planting material is an important prerequisite for the production of a healthy crop of ginger in the field. In the present work we have evaluated the suitability of NCM-ELISA kit, developed at International Potato Center (Crp), Lima, Peru, for detecting bacterial wilt pathogen in ginger. The result indicated that the antibodies developed at crp for potato strain of R. solanacearum was sensitive enough to detect R. solanacearum from ginger, chilli, Chromolaena and tomato. The sensitivity of the kit was determined to be 42 cells per ml of ginger extract when ELISA was performed after enrichment in selective medium. We have also tested the specificity of antibodies and found that the antibodies were specific for R. solanacearu111 .. The extraction protocol (citrate buffer at pH 5.6) developed for potato was found to be suitable for ginger also.